Влияние общественных факторов на студенческую молодежь (мотивационный аспект) - Яковенко, А. (Социология: теория, методы, маркетинг, 2000)
The article presents the motivation factors related to entering and studying at Universities. The whole description, analysis and explanation are based on procedure motivation theories with the help of questionnaires, interviews and open dialogue with students. According to the research results, influence of critical social factors on motivation of todayís University entrants and students can be seen in distinct evolution of their purposes from ideal and moral to mercantile and real.